A well-differentiated B-cell line is permissive for somatic mutation of a transfected immunoglobulin heavy-chain gene. - Zhu, M (1995)
pSV2neo plasmids containing an IgM heavy-chain gene with nonsense mutations in either the variable (V) or the constant (C) region were transfected into four differentiated mouse plasma cell lines: S107 and the NSO fusion partner (myeloma cell lines) and 2C3 and 36.65 (hybridoma cell lines). The frequencies of reversion of the nonsense mutations in multiple independent transfectants were determined with the spot ELISA and rates of reversion were calculated by fluctuation analysis. Mutations in both V and C regions were confirmed by sequence analyses. In the S107 cell line, spontaneous point mutations occurred in the V region at a rate of approximately 5 x 10(-5)/bp per cell generation, > 400-fold higher than the rate of V-region mutation in the NSO cell line and considerably higher than the rates in 2C3 and 36.65 hybridoma cell lines. These studies suggest that S107 is a relatively permissive cell line in which V-region mutations can occur constitutively, even though it represents a late stage of B-cell differentiation. Further, the results show that the construct used contains sufficient information in its flanking and coding sequences to allow a relatively high rate of V-region mutation, at least in the S107 cell line.